An Anterior Abdominal Wall Alveolar Soft Part Sarcoma in a Child: A Case Report - Arthi Anandhan; K Chandramouleeswari; Umadevi Srinivasan (Journal of Clinical and Diagnostic Research, 2025)
Alveolar Soft Part Sarcoma (ASPS) is a rare and aggressive soft-tissue sarcoma, constituting less than 1% of all sarcomas, with a predilection for young adults and occasional paediatric presentations. This case report highlights an eight-year-old girl who presented with a one-month history of a painless swelling in the left anterior abdominal wall. Clinical evaluation and imaging revealed a 4×3.5×2.5 cm enhancing soft-tissue lesion in the left rectus abdominis muscle, raising suspicion of malignancy. Excisional biopsy revealed histological features typical of ASPS, including solid nests of polygonal cells with eosinophilic granular cytoplasm, prominent nucleoli, and pseudo-alveolar architecture. Tumour cells exhibited mild atypia, necrosis, and vascular invasion. Periodic Acid-Schiff (PAS) staining demonstrated intracytoplasmic crystals, and Immunohistochemistry (IHC) confirmed TFE3 nuclear positivity and CD34 expression, confirming the diagnosis of ASPS. ASPS is associated with a specific translocation, der(17)t(x;17)(p11;q25), resulting in ASPSCR1-TFE3 gene fusion, which activates oncogenic pathways such as c-Mesenchymal Epithelial Transition (MET) signalling. The tumour’s propensity for vascular invasion and metastasis contributes to its poor prognosis, with the lungs, brain, and skeleton being the common metastatic sites. Standard chemotherapy is often ineffective, underscoring the importance of early diagnosis and complete surgical resection. This case underscores the diagnostic challenges and emphasises the need for molecular and immunohistochemical studies to distinguish ASPS from mimickers. Furthermore, it highlights the emerging role of targeted therapies and anti-angiogenic agents in improving outcomes for advanced or metastatic disease.